Solar cell and preparation method and application thereof

By using blended inorganic nanoparticles and self-assembled single-molecular materials in perovskite solar cells, the problem of poor interface stability and wetting in perovskite solar cells is solved, and the photoelectric conversion efficiency is improved The preparation process is simplified, suitable for the industrial production of large-area batteries.

CN119173052APending Publication Date: 2024-12-20TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411234674.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In perovskite solar cells, the interface stability and wettability between the nickel oxide hole transport layer and the perovskite layer are poor, which affects the photoelectric conversion efficiency.

Method used

The hole transport layer formed by blended inorganic nanoparticles and self-assembled single-molecular material is used to form a hole transport layer. The self-assembled single-molecular material is anchored on the surface of the inorganic nanoparticles, adjust the interface energy level and improve the interface stability and wettability.

Benefits of technology

It improves the photoelectric conversion efficiency of perovskite solar cells, simplifies the preparation process, reduces costs, and is suitable for the industrial production of large-area batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173052A_ABST
    Figure CN119173052A_ABST
Patent Text Reader

Abstract

The invention relates to a solar cell and a preparation method and application thereof. The solar cell comprises a substrate, a hole transport layer and a perovskite light absorption layer which are stacked in sequence, wherein the hole transport layer comprises inorganic nanoparticles and a self-assembled monomolecular material which are blended, and at least part of the self-assembled monomolecular material is anchored on the surfaces of the inorganic nanoparticles. The hole transport layer is prepared by blending the self-assembled monomolecular material and the inorganic nanoparticles, so that the self-assembled monomolecular material can passivate surface defects of the inorganic nanoparticles and regulate and control the interface energy level, thereby improving the wettability and interface stability of the perovskite light absorption layer and the hole transport layer, and improving the performance of the perovskite light absorption layer and the hole transport layer. And the photoelectric conversion efficiency of the solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solar cells, and in particular to a solar cell and a preparation method and application thereof. Background Art

[0002] Thanks to the development of perovskite materials and film-forming technology, the photoelectric conversion efficiency of perovskite solar cells (PSCs) has been greatly improved in the past decade, for example, the photoelectric conversion efficiency has increased from 3.8% to 25.7%. At present, the development of efficient, stable and low-cost charge transport materials, especially hole transport materials (HTM), is crucial to promote the industrialization of PSCs.

[0003] Inorganic materials such as nickel oxide are widely used in the hole transport layer of PSCs due to their good hole extraction ability, high photothermal stability, and great potential for low-temperature large-scale preparation. However, compared with the perovskite layer, nickel oxide has a lower intrinsic conductivity and insufficient energy level matching, which leads to poor wettability and poor interface stability between the hole transport layer and the perovskite layer, affecting the photoelectric conversion efficiency of perovskite solar cells. Summary of the invention

[0004] Based on this, some embodiments of the present application provide a solar cell, which is beneficial to improving the interface stability and wettability between the hole transport layer and the perovskite layer, thereby helping to improve the photoelectric conversion efficiency of the solar cell.

[0005] In addition, some embodiments of the present invention also provide a method for preparing a solar cell and an application thereof.

[0006] A solar cell comprises a substrate, a hole transport layer and a perovskite light absorption layer which are stacked in sequence;

[0007] The hole transport layer comprises mixed inorganic nanoparticles and self-assembled monomolecular materials, and at least a portion of the self-assembled monomolecular materials are anchored on the surface of the inorganic nanoparticles.

[0008] In some embodiments, the hole transport layer satisfies one or more of the following conditions:

[0009] (1) The mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-5): 100;

[0010] (2) The inorganic nanoparticles include one or more of doped or undoped nickel oxide nanoparticles, cuprous iodide nanoparticles, cuprous thiocyanate nanoparticles, copper oxide nanoparticles, cuprous oxide nanoparticles, copper sulfide nanoparticles and antimony-doped tin oxide nanoparticles;

[0011] (3) The average particle size of the inorganic nanoparticles is 5 nm to 10 nm.

[0012] In some of the embodiments, the mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-4):100.

[0013] In some embodiments, the inorganic nanoparticles include doped or undoped nickel oxide nanoparticles, and the doping elements in the doped nickel oxide nanoparticles include one or more of trivalent nickel, copper, cobalt, manganese, lanthanum, yttrium, magnesium, lithium, zinc, indium and tin.

[0014] In some embodiments, the self-assembled monomolecular material is selected from one or more of the following structural formulas:

[0015] and ;

[0016] In the formula, X 1 , X 2 , Y 1 and Y 2 are each independently selected from hydrogen, C 1 ~C 10 Alkyl, amino, nitro, C 1 ~C 10 Alkoxy, halogen, C 2 ~C 10 Alkenyl and C 1 ~C 10 One of the alkynyl groups;

[0017] R 1 and R 2 are each independently selected from hydrogen and C 1 ~C 10 One of the alkyl groups;

[0018] L 1 and L 2 Each independently selected from C 2 ~C 18 One of an alkylene group and a phenylene group;

[0019] A 1 and A 2 Each is independently an anchoring group.

[0020] In some embodiments, the self-assembled monomolecular material satisfies one or more of the following conditions:

[0021] (1) X 1 , X 2 , Y 1 and Y 2 are each independently selected from hydrogen, C 1~C 6 Alkyl, C 1 ~C 6 Alkoxy, halogen, C 2 ~C 6 Alkenyl and C 2 ~C 6 One of the alkynyl groups;

[0022] (2) R 1 and R 2 Each independently selected from C 1 ~C 6 alkyl;

[0023] (3) L 1 and L 2 Each independently selected from C 2 ~C 6 One of an alkylene group and a phenylene group;

[0024] (4) A 1 and A 2 Each is independently selected from one of the following groups: .

[0025] In some embodiments, the self-assembled monomolecular material is selected from one or more of the following structures: .

[0026] In some embodiments, the hole transport layer is anchored on the substrate surface by the self-assembled monomolecular material; and / or,

[0027] The thickness of the hole transport layer is 10nm-30nm.

[0028] In some embodiments, the solar cell is a single-junction cell, and the solar cell includes a substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, and a counter electrode stacked in sequence; or,

[0029] The solar cell is a stacked cell, and the solar cell comprises: a top cell, a bonding layer and a bottom cell stacked in sequence, the top cell comprises the hole transport layer and the perovskite light absorption layer, and the bonding layer comprises the substrate.

[0030] A method for preparing a solar cell comprises the following steps:

[0031] Obtaining a dispersion comprising inorganic nanoparticles, a self-assembled monomolecular material and a dispersion solvent;

[0032] Applying the dispersion on the surface of the substrate, annealing, and anchoring at least part of the self-assembled monomolecular material on the surface of the inorganic nanoparticles to prepare a hole transport layer;

[0033] A perovskite light-absorbing layer is formed on the surface of the hole transport layer to prepare a solar cell.

[0034] In some embodiments, one or more of the following conditions are met:

[0035] (1) The mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-5): 100;

[0036] (2) The inorganic nanoparticles include one or more of doped or undoped nickel oxide nanoparticles, cuprous iodide nanoparticles, cuprous thiocyanate nanoparticles, copper oxide nanoparticles, cuprous oxide nanoparticles, copper sulfide nanoparticles and antimony-doped tin oxide nanoparticles;

[0037] (3) The self-assembled monomolecular material is selected from one or more of the following structural formulas:

[0038] and ;

[0039] In the formula, X 1 , X 2 , Y 1 and Y 2 are each independently selected from hydrogen, C 1 ~C 10 Alkyl, amino, nitro, C 1 ~C 10 Alkoxy, halogen, C 2 ~C 10 Alkenyl and C 1 ~C 10 One of the alkynyl groups;

[0040] R 1 and R 2 are each independently selected from hydrogen and C 1 ~C 10 One of the alkyl groups;

[0041] L 1 and L 2 Each independently selected from C 2 ~C 18 One of an alkylene group and a phenylene group;

[0042] A 1 and A 2 each independently an anchoring group;

[0043] (4) In the dispersion, the concentration of the inorganic nanoparticles is 15 mg / mL to 30 mg / mL;

[0044] (5) The dispersing solvent includes an alcohol solvent;

[0045] (6) The annealing step includes: heating annealing at 100°C to 150°C for 10 min to 60 min.

[0046] In some embodiments, the doping elements in the doped nickel oxide nanoparticles include one or more of trivalent nickel, copper, cobalt, manganese, lanthanum, yttrium, magnesium, lithium, zinc, indium and tin.

[0047] In some embodiments, the dispersion solvent includes one or more of ethanol and isopropanol.

[0048] A solar cell module comprises a plurality of solar cells connected in series, wherein the solar cells are prepared as described above or by the preparation method described above.

[0049] A photovoltaic component comprises the above-mentioned solar cell, the solar cell prepared by the above-mentioned preparation method or the above-mentioned solar cell module.

[0050] The hole transport layer in the above-mentioned solar cell includes blended inorganic nanoparticles and self-assembled monomolecular materials. By blending the self-assembled monomolecular materials and the inorganic nanoparticles, at least part of the self-assembled monomolecular materials are anchored on the surface of the inorganic nanoparticles, so that the self-assembled monomolecular materials can passivate the surface defects of the inorganic nanoparticles and regulate the interface energy level; at the same time, compared with the sequential deposition of inorganic hole transport layers such as nickel oxide hole transport layers and self-assembled monolayers, the above-mentioned hole transport layers in some embodiments of the present application can improve the passivation of defects while having a relatively low molecular coverage, thereby improving the wettability and interface stability of the perovskite layer on the hole transport layer, thereby improving the photoelectric conversion efficiency of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0052] Figure 1 A schematic diagram of the structure of a solar cell according to some embodiments of the present application;

[0053] Figure 2 This is a process flow chart of a method for preparing a solar cell according to some embodiments of the present application. DETAILED DESCRIPTION

[0054] In order to facilitate the understanding of the present application, the present application will be described more comprehensively below in conjunction with the specific embodiments. The preferred embodiments of the present application are provided in the specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0056] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:

[0057] In this application, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features.

[0058] In the description of the present application, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0059] In this application, "one or several" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0060] In this application, the percentage concentration involved, unless otherwise specified, refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0061] The words "optionally" and the like in this application refer to embodiments of the present application that may provide certain beneficial effects in certain cases. However, other embodiments may also be optional under the same or other circumstances. In addition, the statement of one or more optional embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this application.

[0062] In this document, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent technical solutions are related in terms of the content covered, but should not be understood as a limitation on the previous technical solution, nor can it be understood as a limitation on the protection scope of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0063] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0064] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0065] The terms "including" and "having" and any variations thereof in the embodiments of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or components that are inherent to these processes, methods, products, or devices.

[0066] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.

[0067] The term "alkyl" refers to a saturated hydrocarbon containing primary (normal) carbon atoms, or secondary carbon atoms, or tertiary carbon atoms, or quaternary carbon atoms, or a combination thereof. Phrases containing this term, such as "C 1 ~C 6 "Alkyl" refers to an alkyl group containing 1 to 6 carbon atoms, each occurrence of which can be independently C 1 Alkyl, C 2 Alkyl, C 3 Alkyl, C 4 Alkyl, C 5 Alkyl, C6 Suitable examples include, but are not limited to, methyl (Me, -CH 3 ), ethyl (Et, -CH 2 CH 3 ), 1-propyl (n-Pr, n-propyl, -CH 2 CH 2 CH 3 ), 2-propyl (i-Pr, i-propyl, -CH (CH 3 ) 2 ), 1-butyl (n-Bu, n-butyl, -CH 2 CH 2 CH 2 CH 3 ), 2-methyl-1-propyl (i-Bu, i-butyl, -CH 2 CH(CH 3 ) 2 ), 2-butyl (s-Bu, s-butyl, -CH (CH 3 )CH 2 CH 3 ), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH 3 ) 3 ), 1-pentyl (n-pentyl, -CH 2 CH 2 CH 2 CH 2 CH 3 ), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH 2 CH 3 ) 2 ), 2-methyl-2-butyl (-C(CH 3 ) 2 CH 2 CH 3 ), 3-methyl-2-butyl (-CH(CH 3 )CH(CH 3 ) 2 ), 3-methyl-1-butyl (-CH 2 CH 2 CH(CH 3 ) 2 ), 2-methyl-1-butyl (-CH 2 CH(CH 3 )CH 2 CH 3 )、1-hexyl (-CH 2 CH 2 CH 2 CH 2 CH2 CH 3 ), 2-hexyl (-CH(CH 3 )CH 2 CH 2 CH 2 CH 3 )、3-hexyl(-CH(CH 2 CH 3 )(CH 2 CH 2 CH 3 ))、2-methyl-2-pentyl (-C(CH 3 ) 2 CH 2 CH 2 CH 3 ), 3-methyl-2-pentyl (-CH(CH 3 )CH(CH 3 )CH 2 CH 3 ), 4-methyl-2-pentyl (-CH(CH 3 )CH 2 CH(CH 3 ) 2 ), 3-methyl-3-pentyl (-C(CH 3 )(CH 2 CH 3 ) 2 ), 2-methyl-3-pentyl (-CH(CH 2 CH 3 )CH(CH 3 ) 2 )、2,3-dimethyl-2-butyl (-C(CH 3 ) 2 CH(CH 3 ) 2 )、3,3-dimethyl-2-butyl (-CH(CH 3 )C(CH 3 ) 3 .

[0068] The term "alkoxy" refers to a group having an -O-alkyl group, i.e., an alkyl group as defined above attached via an oxygen atom to a parent core structure. Phrases containing this term, such as "C 1 ~C 6 "Alkoxy" means that the alkyl part contains 1 to 6 carbon atoms, each occurrence can be independently C 1 Alkoxy, C 4 Alkoxy, C 5 Alkoxy, C 6 Suitable examples include, but are not limited to, methoxy (—O—CH 3or -OMe), ethoxy (-O-CH 2 CH 3 or -OEt) and tert-butyloxy (-OC(CH 3 ) 3 or -OtBu).

[0069] "Alkenyl" refers to a group containing at least one unsaturated site, i.e., a carbon-carbon sp 2 A hydrocarbon containing a double-bonded positive, secondary, or tertiary carbon atom. Phrases containing this term, such as "C 2 ~C 6 "Alkenyl" refers to an alkenyl group containing 2 to 6 carbon atoms, each occurrence of which can be independently C 2 Alkenyl, C 3 Alkenyl, C 4 Alkenyl, C 5 Alkenyl, C 6 Suitable examples include, but are not limited to, vinyl (-CH=CH 2 ), allyl (-CH 2 CH=CH 2 ) and 5-hexenyl (-CH 2 CH 2 CH 2 CH 2 CH=CH 2 ).

[0070] "Alkynyl" refers to a hydrocarbon containing a normal, secondary, tertiary, or cyclic carbon atom having at least one site of unsaturation, i.e., a carbon-carbon sp triple bond. Phrases containing this term, such as "C 2 ~C 6 "Alkenyl" refers to an alkynyl group containing 2 to 6 carbon atoms, each occurrence of which can be independently C 2 Alkynyl, C 3 Alkynyl, C 4 Alkynyl, C 5 Alkynyl, C 6 Suitable examples include, but are not limited to, ethynyl (-C≡CH) and propargyl (-CH 2 C≡CH).

[0071] "Halogen" or "halo" refers to F, Cl, Br or I.

[0072] "Alkylene" refers to a hydrocarbon group having two monovalent radical centers derived from an alkyl group by removing a hydrogen atom, which may be a saturated branched alkyl group or a saturated straight chain alkyl group. For example, "C 2 ~C 18 "Alkylene" means that the alkyl portion contains 2 to 18 carbon atoms, each occurrence can be independently C2 Alkylene, C 4 Alkylene, C 5 Alkylene, C 6 Alkylene, C 7 Alkylene, C 8 Alkylene, C 10 Alkylene, C 12 Alkylene, C 14 Alkylene, C 16 Alkylene, C 18 Suitable examples include, but are not limited to: 1,1-ethyl (-CH(CH 3 )-), 1,2-ethyl (-CH 2 CH 2 -), 1,1-propyl (-CH(CH 2 CH 3 )-), 1,2-propyl (-CH 2 CH(CH 3 )-), 1,3-propyl (-CH 2 CH 2 CH 2 -) and 1,4-butyl (-CH 2 CH 2 CH 2 CH 2 -)wait.

[0073] "Amino" refers to a derivative of ammonia having the formula -N(X) 2 The structural features of wherein each "X" is independently H, substituted or unsubstituted alkyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted heterocyclyl, etc. Non-limiting types of amino groups include -NH 2 、-N(alkyl) 2 、-NH(alkyl), -N(cycloalkyl) 2 、-NH(cycloalkyl), -N(heterocyclic) 2 、-NH(heterocyclic group), -N(aryl group) 2 , -NH(aryl), -N(alkyl)(aryl), -N(alkyl)(heterocyclyl), -N(cycloalkyl)(heterocyclyl), -N(aryl)(heteroaryl), -N(alkyl)(heteroaryl), and the like.

[0074] A first aspect of the present application provides a solar cell, comprising a substrate, a hole transport layer and a perovskite light absorption layer stacked in sequence;

[0075] The hole transport layer comprises mixed inorganic nanoparticles and self-assembled monomolecular materials, and at least a portion of the self-assembled monomolecular materials are anchored on the surface of the inorganic nanoparticles.

[0076] The hole transport layer in the above-mentioned solar cell includes blended inorganic nanoparticles and self-assembled monomolecular materials. By blending the self-assembled monomolecular materials and the inorganic nanoparticles, at least part of the self-assembled monomolecular materials are anchored on the surface of the inorganic nanoparticles, so that the self-assembled monomolecular materials can passivate the surface defects of the inorganic nanoparticles and regulate the interface energy level, thereby improving the wettability and interface stability of the perovskite light absorption layer and the hole transport layer, thereby improving the photoelectric conversion efficiency of the solar cell.

[0077] In traditional technology, in order to improve the wettability and interface stability between the hole transport layer and the perovskite light absorbing layer, an inorganic hole transport layer such as a nickel oxide hole transport layer is usually prepared first, and then a SAM layer (monomolecule self-assembled layer) is prepared. However, the above method, on the one hand, increases the preparation steps, which is not conducive to industrial application; on the other hand, the coverage of SAM on the nickel oxide substrate is poor, and large-area preparation is difficult, resulting in low module efficiency of large-area devices, which is not suitable for industrialization, and two-layer preparation, usually with high coverage; there will be excess molecules affecting the wettability, and the improvement effect on wettability and interface stability is limited. Based on this, the inventors of this application further improved the wettability and interface stability between the hole transport layer and the perovskite light absorbing layer by blending inorganic nanoparticles and self-assembled monomolecular materials to form a hole transport layer, which is beneficial to improving the photoelectric conversion efficiency of perovskite solar cells. In addition, compared with traditional technologies, the process preparation process is reduced, the cost is reduced, and it is conducive to the preparation of large-area batteries.

[0078] In addition, inorganic nanoparticles such as nickel oxide nanoparticles contain a large number of Ni vacancies on their surfaces, which will induce the formation of strong oxidizing Ni on the film surface. 3+ , causing it to chemically react with the subsequently deposited perovskite layer, promoting the degradation of the material at the interface between nickel oxide and perovskite, and ultimately affecting the carrier lifetime of the perovskite film and the photoelectric conversion efficiency of the perovskite solar cell. In some embodiments of the present application, the surface defects of the inorganic nanoparticles are passivated by self-assembled monomolecular materials to avoid the degradation of the material at the interface between the inorganic nanoparticles and the perovskite, which is beneficial to improve the carrier lifetime and the photoelectric conversion efficiency of the perovskite solar cell.

[0079] It can be understood that both inorganic nanoparticles and self-assembled monomolecular materials have hole transport properties.

[0080] In some embodiments, the self-assembled monomolecular material has an anchoring group, and the anchoring group includes one of a phosphate group and a carboxylic acid group.

[0081] In some embodiments, the self-assembled monomolecular material is selected from one or more of the following structural formulas:

[0082] and ;

[0083] In the formula, X 1 , X 2 , Y 1 and Y 2 Each is independently selected from one of hydrogen, alkyl, amino, nitro, alkoxy, halogen, alkenyl and alkynyl;

[0084] R 1 and R 2 are each independently selected from hydrogen and C 1 ~C 10 One of the alkyl groups;

[0085] L 1 and L 2 Each independently selected from C 2 ~C 18 One of an alkylene group and a phenylene group;

[0086] A 1 and A 2 Each is independently an anchoring group.

[0087] In some embodiments, X 1 , X 2 , Y 1 and Y 2 are each independently selected from hydrogen, C 1 ~C 6 Alkyl, C 1 ~C 6 Alkoxy, halogen, C 2 ~C 6 Alkenyl and C 2 ~C 6 Further, X 1 , X 2 , Y 1 and Y 2 are each independently selected from hydrogen, C 1 ~C 6 Alkyl, C 1 ~C 6 One of alkoxy and halogen. In one embodiment, X 1 and Y 1 Same. X 2 and Y 2 same.

[0088] Optionally, X 1 and Y 1 are each independently selected from hydrogen, C 1 ~C 6 Alkyl and C 1 ~C 6 One of the alkoxy groups. 2 and Y2 Each independently selected from C 1 ~C 6 One of alkyl and halogen.

[0089] In some embodiments, R 1 and R 2 Each independently selected from C 1 ~C 6 alkyl.

[0090] In some embodiments, L 1 and L 2 Each independently selected from C 2 ~C 6 One of an alkylene group and a phenylene group. Further, L 1 and L 2 Each independently selected from C 2 ~C 6 Alkylene.

[0091] In some embodiments, A 1 and A 2 Each is independently selected from one of the following groups: .

[0092] In some embodiments, the self-assembled monomolecular material has the following structural formula:

[0093] ;

[0094] Where, X 2 and Y 2 are each independently selected from one of hydrogen, alkyl, amino, nitro, alkoxy, halogen, alkenyl and alkynyl; further, X 2 and Y 2 are each independently selected from hydrogen, C 1 ~C 6 Alkyl, C 1 ~C 6 Alkoxy, halogen, C 2 ~C 6 Alkenyl and C 2 ~C 6 Furthermore, X 2 and Y 2 Each independently selected from C 1 ~C 6 One of alkyl and halogen.

[0095] R 1 and R 2 are each independently selected from hydrogen and C 1 ~C 10 One of the alkyl groups; further, R1 and R 2 Each independently selected from C 1 ~C 6 One of the alkyl groups. Specifically, R 1 and R 2 same.

[0096] L 2 Selected from C 2 ~C 18 One of an alkylene group and a phenylene group. Further, L 2 Selected from C 2 ~C 6 Alkylene.

[0097] A 2 is an anchoring group. Further, A 2 Includes one of a phosphate group and a carboxylic acid group.

[0098] In some other embodiments, the self-assembled monomolecular material has the following structural formula:

[0099] ;

[0100] Where, X 1 , Y 1 are each independently selected from one of hydrogen, alkyl, amino, nitro, alkoxy, halogen, alkenyl and alkynyl; further, X 1 , Y 1 are each independently selected from hydrogen, C 1 ~C 6 Alkyl, C 1 ~C 6 Alkoxy, halogen, C 2 ~C 6 Alkenyl and C 2 ~C 6 Further, X 1 , Y 1 are each independently selected from hydrogen, C 1 ~C 6 Alkyl and C 1 ~C 6 In one embodiment, X 1 and Y 1 same.

[0101] L 1 Selected from C 2 ~C 18 One of an alkylene group and a phenylene group; further, L 1 Selected from C 2 ~C 6 One of an alkylene group and a phenylene group. Further, L1 Selected from C 2 ~C 6 Alkylene.

[0102] A 1 is an anchoring group. Further, A 1 Includes one of a phosphate group and a carboxylic acid group.

[0103] In some embodiments, the self-assembled monomolecular material is selected from one or more of the following structures: .

[0104] In some embodiments, the inorganic nanoparticles include one or more of doped or undoped nickel oxide nanoparticles, cuprous iodide nanoparticles, cuprous thiocyanate nanoparticles, copper oxide nanoparticles, cuprous oxide nanoparticles, copper sulfide nanoparticles, and antimony-doped tin oxide nanoparticles. Specifically, the doping elements in the doped nickel oxide nanoparticles include one or more of trivalent nickel, copper, cobalt, manganese, lanthanum, yttrium, magnesium, lithium, zinc, indium, and tin. Optionally, the inorganic nanoparticles include doped or undoped nickel oxide nanoparticles.

[0105] In some embodiments, the average particle size of the inorganic nanoparticles is 5 nm to 10 nm.

[0106] In some embodiments, the mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-5):100. For example, the mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles may be, but is not limited to, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, 5:100 or a range consisting of any two of these values. When the mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is less than 1:100, the amount of the self-assembled monomolecular material is small, and the passivation effect on the inorganic nanoparticles is limited, thereby limiting the improvement of the photoelectric conversion efficiency of the solar cell. When the mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is greater than 5:100, the dispersibility of the nanoparticles will be affected, resulting in a decrease in the hole transport performance. Optionally, the mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-4):100. Optionally, the mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1.5-3.5):100.

[0107] In some embodiments, the inorganic nanoparticles include doped or undoped nickel oxide nanoparticles, and the self-assembled monomolecular material is selected from one or more of the following structures: .

[0108] Further, in some embodiments, the inorganic nanoparticles include doped or undoped nickel oxide nanoparticles, and the self-assembled monomolecular material is selected from , and One or more of the .

[0109] In some embodiments, at least part of the self-assembled monomolecular material is anchored on the surface of the inorganic nanoparticles. In the process of preparing the hole transport layer, the anchoring groups of the self-assembled monomolecular material interact with the hydroxyl groups on the surface of the inorganic nanoparticles and are anchored on the surface of the inorganic nanoparticles. The above arrangement is conducive to passivating the surface defects of the inorganic nanoparticles.

[0110] In some embodiments, the thickness of the hole transport layer is 10 nm to 30 nm. For example, the thickness of the hole transport layer can be, but is not limited to, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, or a range consisting of any two of these values.

[0111] In some embodiments, the hole transport layer is anchored on the surface of the substrate through the self-assembled monomolecular material.

[0112] In some embodiments, the substrate includes a transparent conductive oxide.

[0113] In some embodiments, the solar cell is a single junction cell, and the solar cell includes a substrate, a hole transport layer, a perovskite light absorption layer, an electron transport layer, and a counter electrode stacked in sequence. The substrate includes a substrate and a transparent conductive oxide electrode disposed on the surface of the substrate. The substrate may be, but is not limited to, glass.

[0114] It can be understood that, in this article, sequential stacking only refers to the stacking order between each layer, but is not limited to only containing the above-mentioned layers, and other layers can be stacked between each layer.

[0115] In some embodiments, the solar cell is of an inverted structure (pin type), and the base includes a substrate and a transparent conductive oxide electrode disposed on the surface of the substrate. Specifically, the material of the transparent conductive oxide electrode may be, but is not limited to, one or more of oxides such as indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), indium-doped zinc oxide (IZO), fluorine-doped tin oxide (FTO), indium tungsten oxide (IWO), and indium cerium oxide (ICO).

[0116] The counter electrode includes one or more of a silver electrode, a copper electrode, a conductive oxide electrode and a carbon electrode. It is understood that only a few common counter electrodes are given above, but they are not limited thereto, and can also be other materials commonly used in the art, which are not particularly limited here.

[0117] In some embodiments, the material of the perovskite light absorbing layer includes ABX 3 , where the A-position cation (A+ ) including formamidinium ion (FA + ), cesium ion (Cs + ) and methylamine ion (MA + ) one or more of them.

[0118] In some embodiments, B 2+ Including lead ions (Pb 2+ ) and tin (Sn 2+ ) one or more of them.

[0119] In some embodiments, X - including halogen ions, specifically, X - Including bromide ion (Br - ) and iodide ion (I - ) one or more of them.

[0120] In some embodiments, the thickness of the perovskite layer may be commonly used in the art, such as 400 nm to 500 nm. For example, the thickness of the perovskite layer may be, but is not limited to, 400 nm, 410 nm, 420 nm, 430 nm, 440 nm, 450 nm, 460 nm, 470 nm, 480 nm, 490 nm, 500 nm, or a range consisting of any two of these values.

[0121] In some embodiments, the material of the electron transport layer is selected from one or more of [6,6]-phenyl-C61-butyric acid methyl ester, C60 and tin oxide. It can be understood that only a few common materials for the electron transport layer are given above, but they are not limited thereto, and other materials commonly used in the art can also be used, which are not particularly limited here.

[0122] In some of the embodiments, a hole blocking layer is further provided between the electron transport layer and the counter electrode.

[0123] In some embodiments, the material of the hole blocking layer is selected from one or more of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline and zirconium acetylacetonate. It can be understood that only a few common hole blocking layer materials are given above, but they are not limited thereto, and other materials commonly used in the art can also be used, which are not particularly limited here.

[0124] See also Figure 1 The solar cell 200 of some embodiments of the present application includes a substrate 210, a hole transport layer 220, a perovskite light absorbing layer 230, an electron transport layer 240, a hole blocking layer 250 and a counter electrode 260 which are stacked in sequence.

[0125] It can be understood that the above only provides a structure of a solar cell, but is not limited thereto.

[0126] In some other embodiments, the solar cell is a stacked cell, which includes: a top cell, a bonding layer and a bottom cell stacked in sequence, the top cell includes the hole transport layer and the perovskite light absorption layer, and the bonding layer includes a substrate.

[0127] It is understood that the specific tandem battery can be selected according to actual needs. For example, the tandem battery can be, but is not limited to, a perovskite / crystalline silicon tandem battery, a full perovskite tandem battery, a perovskite / organic tandem battery, a perovskite / CIGS tandem battery, a perovskite / CdTe tandem battery, a perovskite / GaAs tandem battery, etc.

[0128] A second aspect of the present application provides a method for preparing a solar cell, comprising the following steps:

[0129] Obtaining a dispersion comprising inorganic nanoparticles, a self-assembled monomolecular material and a dispersion solvent;

[0130] Applying a dispersion on the surface of a substrate and annealing to anchor at least a portion of the self-assembled monomolecular material on the surface of the inorganic nanoparticles to prepare a hole transport layer;

[0131] A perovskite light-absorbing layer is formed on the surface of the hole transport layer to prepare a solar cell.

[0132] The specific self-assembled monomolecular materials and inorganic nanoparticles are as described above and will not be described in detail here.

[0133] In some embodiments, in the dispersion, the concentration of the inorganic nanoparticles is 15 mg / mL to 30 mg / mL. For example, the concentration of the inorganic nanoparticles may be, but is not limited to, 15 mg / mL, 18 mg / mL, 20 mg / mL, 22 mg / mL, 25 mg / mL, 28 mg / mL, 30 mg / mL, or a range consisting of any two of these values.

[0134] In some embodiments, the dispersion solvent includes an alcohol solvent, and specifically, the dispersion solvent includes one or more of ethanol and isopropanol.

[0135] In some embodiments, the step of preparing the dispersion includes: ultrasonicating the inorganic nanoparticles and the self-assembled monomolecular material in a dispersion solvent, filtering, and obtaining the dispersion. Specifically, the ultrasonication time is 15 min to 30 min.

[0136] In some embodiments, the annealing step includes: heating annealing at 100° C. to 150° C. for 10 min to 60 min.

[0137] In some embodiments, the dispersion is applied to the substrate surface by spin coating. The specific spin coating process may be commonly used in the art, for example, spin coating at a rotation speed of 5000 rpm for 30 seconds.

[0138] In some embodiments, the solar cell is a single junction cell, see Figure 2 , the method for preparing a solar cell in some embodiments of the present application comprises the following steps:

[0139] Step S110: applying the above dispersion on the surface of the substrate, annealing, and preparing a hole transport layer.

[0140] In some embodiments, the thickness of the hole transport layer is 10 nm to 30 nm.

[0141] Step S120: forming a perovskite light absorbing layer on the surface of the hole transport layer.

[0142] In some embodiments, a solution method is used to form a perovskite light absorbing layer. In some embodiments, a precursor solution containing a first perovskite material and a second perovskite material is applied to the surface of a hole transport layer and annealed to prepare a perovskite light absorbing layer. The first perovskite material is selected from one or more of a lead halide salt and a tin halide salt, and the second perovskite material is selected from one or more of a formamidine halide salt, a methylamine halide salt, and a cesium halide salt.

[0143] In some embodiments, the annealing temperature is 100° C. and the time is 40 minutes. It can be understood that the above only provides one annealing temperature and time, but is not limited thereto, and can also be adjusted according to the common methods in the art.

[0144] Step S130: forming an electron transport layer on the surface of the perovskite light absorbing layer.

[0145] In some embodiments, the material of the electron transport layer is selected from one or more of [6,6]-phenyl-C61-butyric acid methyl ester, C60 and tin oxide. The electron transport layer is formed by a solution method. The specific steps can be commonly used in the art and are not particularly limited here.

[0146] Step S140: forming a hole blocking layer on the surface of the electron transport layer.

[0147] In some embodiments, the material of the hole blocking layer is selected from one or more of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline and zirconium acetylacetonate. The hole blocking layer is formed by a solution method. The specific steps can be commonly used in the art and are not particularly limited here.

[0148] Step S150: forming a counter electrode on the surface of the hole blocking layer to prepare a solar cell.

[0149] In some embodiments, the material of the counter electrode is selected from one or more of silver, copper, conductive oxide and carbon electrode. The counter electrode is formed by evaporation. The specific steps can be commonly used in the art and are not particularly limited here.

[0150] Figure 2 This is a schematic diagram of a process for preparing a solar cell according to an embodiment of the present application. It should be understood that although Figure 2 The steps in the flowchart are shown in sequence as indicated by the arrows, but these steps are not necessarily performed in the order indicated by the arrows. Unless otherwise specified in this document, there is no strict order restriction for the execution of these steps, and they can be performed in other orders. Figure 2 At least part of the steps may include multiple sub-steps or multiple stages. These sub-steps or stages are not necessarily executed at the same time, but can be executed at different times. The order of execution is not necessarily sequential, but can be executed in turn or alternately with other steps or at least part of other sub-steps or stages.

[0151] It can be understood that the above only provides a preparation method for a solar cell that is a single-junction cell. The preparation method for a solar cell that is a stacked cell can be obtained by referring to the above method and will not be repeated here.

[0152] A third aspect of the present application provides a solar cell module, comprising a plurality of solar cells connected in series.

[0153] A fourth aspect of the present application provides a photovoltaic assembly, comprising the above-mentioned solar cell or the above-mentioned solar cell module.

[0154] In some embodiments, the photovoltaic module includes a photovoltaic glass, a first encapsulation film, a battery, a second encapsulation film, and a photovoltaic backsheet stacked in sequence. In other embodiments, the photovoltaic module includes a first photovoltaic glass, a first encapsulation film, a battery, a second encapsulation film, and a second photovoltaic glass stacked in sequence.

[0155] In order to make the purpose and advantages of the present application clearer, the solar cell of the present application and its effects are further described in detail in combination with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and shall not be used to limit the present application. The following embodiments do not include other components except unavoidable impurities unless otherwise specified. The drugs and instruments used in the embodiments are conventionally selected in the art unless otherwise specified. The experimental methods for which specific conditions are not specified in the embodiments are implemented according to conventional conditions, such as the conditions described in the literature and books or the methods recommended by the manufacturer.

[0156] Example 1

[0157] This embodiment provides a perovskite solar cell, and the preparation steps are as follows:

[0158] (1) The TCO conductive glass was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min respectively, and then dried in a drying oven at 75°C for later use. The dried TCO conductive glass was treated in a UV ozone machine for 25 min to remove organic impurities on its surface and optimize its surface wettability.

[0159] (2) 30 mg of nickel oxide nanoparticles and 1 mg of self-assembled monomolecular material (structural formula: ) was dispersed in 1 mL of isopropanol solution and ultrasonicated for 20 min. After the ultrasonication, it was filtered with a 220 nm PTFE filter to obtain a dispersion. 30 μL of the above dispersion was added dropwise to the TCO conductive glass and spin-coated at 5000 rpm for 30 s. Then the TCO conductive glass was placed on a hot stage and heated and annealed at 100 ° C for 10 min to obtain a hole transport layer with a thickness of 20 nm.

[0160] (3) Dissolve 722.08 mg of lead iodide and 238.50 mg of iodomethylamine solid in 1 mL of N,N-dimethylformamide (DMF) and stir at room temperature until completely dissolved to obtain a perovskite precursor solution. In a nitrogen glove box, take 30 μL of the perovskite precursor solution and drop it onto the surface of the conductive glass with a hole transport layer formed on it. First, spin coat it at 1000 rpm for 10 seconds, then spin coat it at 5000 rpm for 30 seconds. After 25 seconds, quickly drop 125 μL of chlorobenzene, then place the TCO conductive glass on a hot plate and heat and anneal it at 100°C for 40 minutes to form a perovskite light-absorbing layer with a thickness of 500 nm.

[0161] (4) Dissolve 20 mg of methanefullerene phenyl-C61-butyric acid methyl ester (PCBM) in 1 mL of chlorobenzene and stir at room temperature to obtain [6,6]-phenyl-C61-butyric acid methyl ester solution. Take 30 μL of [6,6]-phenyl-C61-butyric acid methyl ester solution and drop it on the ITO conductive glass with the perovskite light absorption layer formed on it. Spin-coat it at 3000 rpm for 60 seconds to form an electron transport layer with a thickness of 30 nm.

[0162] (5) Dissolve 0.5 mg of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) in 1 mL of isopropanol and stir at room temperature to obtain a hole blocking layer solution. Take 40 μL of the hole blocking layer solution and drop it onto the electron transport layer. Spin-coat at 5000 rpm for 35 s to form a hole blocking layer with a thickness of 6 nm.

[0163] (6) Transfer the TCO conductive glass forming the hole blocking layer, electron transport layer, perovskite light absorbing layer, and hole transport layer to the vacuum coating instrument and wait until the vacuum degree is 3×10 -4 A silver electrode was evaporated at 500 nm Pa to form a silver electrode with a thickness of 100 nm on the hole blocking layer to obtain the perovskite solar cell of this embodiment.

[0164] Embodiment 2 to Embodiment 8

[0165] Embodiments 2 to 8 provide a perovskite solar cell, respectively, and the preparation steps are similar to those of Embodiment 1, except that the structure of the self-assembled monomolecular material in the hole transport layer of step (2) is different. In the hole transport layer of Embodiments 2 to 8, the structural formulas of the self-assembled monomolecular material are shown in Formulas 2 to 8, respectively:

[0166] .

[0167] Example 9

[0168] This embodiment provides a perovskite solar cell, and the preparation steps are similar to those of embodiment 1, except that in step (2), the masses of nickel oxide nanoparticles and self-assembled monomolecular materials are different. In this embodiment, "30 mg of nickel oxide nanoparticles and 0.5 mg of self-assembled monomolecular materials" are used to replace "30 mg of nickel oxide nanoparticles and 1 mg of self-assembled monomolecular materials" in embodiment 1.

[0169] Example 10

[0170] This embodiment provides a perovskite solar cell, and the preparation steps are similar to those of embodiment 1, except that in step (2), the masses of nickel oxide nanoparticles and self-assembled monomolecular materials are different. In this embodiment, "30 mg of nickel oxide nanoparticles and 0.3 mg of self-assembled monomolecular materials" are used to replace "30 mg of nickel oxide nanoparticles and 1 mg of self-assembled monomolecular materials" in embodiment 1.

[0171] Embodiment 11

[0172] This embodiment provides a perovskite solar cell, and the preparation steps are similar to those of embodiment 1, except that in step (2), the masses of nickel oxide nanoparticles and self-assembled monomolecular materials are different. In this embodiment, "30 mg of nickel oxide nanoparticles and 1.5 mg of self-assembled monomolecular materials" are used to replace "30 mg of nickel oxide nanoparticles and 1 mg of self-assembled monomolecular materials" in embodiment 1.

[0173] Comparative Example 1

[0174] Comparative Example 1 provides a perovskite solar cell, and the preparation steps are similar to those of Example 1, except that step (2) is different, and the hole transport layer of Comparative Example 1 does not contain a self-assembled monomolecular material. Step (2) of Comparative Example 1 is specifically as follows:

[0175] 30 mg of nickel oxide nanoparticles were dispersed in 1 mL of isopropanol solution and ultrasonicated for 20 min. After the ultrasonication, the dispersion was filtered with a 220 nm PTFE filter to obtain a dispersion. 30 μL of the above dispersion was added dropwise to the TCO conductive glass and spin-coated at 5000 rpm for 30 s. The TCO conductive glass was then placed on a hot plate and heated and annealed at 100 ° C for 10 min to obtain a hole transport layer with a thickness of 20 nm.

[0176] Comparative Example 2

[0177] Comparative Example 2 provides a perovskite solar cell, and the preparation steps are as follows:

[0178] (1) The TCO conductive glass was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min respectively, and then dried in a drying oven at 75°C for later use. The dried TCO conductive glass was treated in a UV ozone machine for 25 min to remove organic impurities on its surface and optimize its surface wettability.

[0179] (2) Disperse 30 mg of nickel oxide nanoparticles in 1 mL of isopropanol solution and ultrasonicate for 20 min. Filter with a 220 nm PTFE filter to obtain a nickel oxide dispersion. Take 30 μL of the above nickel oxide dispersion and drop it on the TCO conductive glass. Spin coat at 5000 rpm for 30 s. Then place the TCO conductive glass on a hot plate and heat anneal at 100 °C for 10 min to obtain a hole transport layer with a thickness of 20 nm.

[0180] (3) 1 mg of self-assembled monomolecular material (structural formula: ) was dispersed in 1 mL of isopropanol solution and ultrasonicated for 20 min. After the ultrasonication, it was filtered with a 220 nm PTFE filter to obtain a self-assembled monomolecular dispersion. 30 μL of the above self-assembled monomolecular dispersion was added dropwise to the surface of the hole transport layer and spin-coated at 5000 rpm for 30 s. Then, the TCO conductive glass was placed on a hot stage and heated and annealed at 100 ° C for 10 min to obtain a self-assembled monolayer with a thickness of 1 nm.

[0181] (4) Dissolve 722.08 mg of lead iodide and 238.50 mg of iodomethylamine solid in 1 mL of N,N-dimethylformamide (DMF) and stir at room temperature until completely dissolved to obtain a perovskite precursor solution. In a nitrogen glove box, take 30 μL of the perovskite precursor solution and drop it onto the surface of the conductive glass with a self-assembled monolayer formed on it. First, spin coat it at 1000 rpm for 10 seconds, then spin coat it at 5000 rpm for 30 seconds. After 25 seconds, quickly drop 125 μL of chlorobenzene, then place the TCO conductive glass on a hot plate and heat and anneal it at 100°C for 40 minutes to form a perovskite light-absorbing layer with a thickness of 500 nm.

[0182] (5) Dissolve 20 mg of methanefullerene phenyl-C61-butyric acid-methyl ester (PCBM) in 1 mL of chlorobenzene and stir at room temperature to obtain [6,6]-phenyl-C61-butyric acid methyl ester solution. Take 30 μL of [6,6]-phenyl-C61-butyric acid methyl ester solution and drop it on the ITO conductive glass with the perovskite light absorption layer formed on it. Spin-coat it at 3000 rpm for 60 seconds to form an electron transport layer with a thickness of 30 nm.

[0183] (6) Dissolve 0.5 mg of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) in 1 mL of isopropanol and stir at room temperature to obtain a hole blocking layer solution. Take 40 μL of the hole blocking layer solution and drop it onto the electron transport layer. Spin-coat at 5000 rpm for 35 s to form a hole blocking layer with a thickness of 6 nm.

[0184] (7) Transfer the TCO conductive glass forming the hole blocking layer, electron transport layer, perovskite light absorbing layer, and hole transport layer to the vacuum coating instrument and wait until the vacuum degree is 3×10 -4 A silver electrode was evaporated at 400 nm Pa to form a silver electrode with a thickness of 100 nm on the hole blocking layer to obtain the perovskite solar cell of Comparative Example 2.

[0185] The performance data of the perovskite solar cells prepared in the above embodiments and comparative examples are shown in Table 1 below.

[0186] Table 1

[0187]

[0188] As can be seen from Table 1, compared with Comparative Examples 1 and 2, the hole transport layer prepared by the embodiment of the present invention using inorganic nanoparticles modified with self-assembled monomolecular materials (SAM) having hole transport capability can improve the photoelectric conversion efficiency and fill factor of the device.

[0189] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0190] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.

Claims

1. A solar cell, characterized in that: It includes a substrate, a hole transport layer and a perovskite light absorbing layer which are stacked in sequence; The hole transport layer comprises mixed inorganic nanoparticles and self-assembled monomolecular materials, and at least a portion of the self-assembled monomolecular materials are anchored on the surface of the inorganic nanoparticles.

2. The solar cell according to claim 1, characterized in that The hole transport layer satisfies one or more of the following conditions: (1) The mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-5): 100; (2) The inorganic nanoparticles include one or more of doped or undoped nickel oxide nanoparticles, cuprous iodide nanoparticles, cuprous thiocyanate nanoparticles, copper oxide nanoparticles, cuprous oxide nanoparticles, copper sulfide nanoparticles and antimony-doped tin oxide nanoparticles; (3) The average particle size of the inorganic nanoparticles is 5 nm to 10 nm.

3. The solar cell according to claim 2, characterized in that: The mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-4):100; and / or, The inorganic nanoparticles include doped or undoped nickel oxide nanoparticles, and the doping elements in the doped nickel oxide nanoparticles include one or more of trivalent nickel, copper, cobalt, manganese, lanthanum, yttrium, magnesium, lithium, zinc, indium and tin.

4. The solar cell according to any one of claims 1 to 3, characterized in that: The self-assembled monomolecular material is selected from one or more of the following structural formulas: and ; In the formula, X1, X2, Y1 and Y2 are each independently selected from hydrogen, C1~C 10 Alkyl, amino, nitro, C1~C 10 Alkoxy, halogen, C2~C 10 Alkenyl and C1~C 10 One of the alkynyl groups; R1 and R2 are each independently selected from hydrogen and C1~C 10 One of the alkyl groups; L1 and L2 are each independently selected from C2 to C 18 One of an alkylene group and a phenylene group; A1 and A2 are each independently an anchoring group.

5. The solar cell according to claim 4, characterized in that: The self-assembled monomolecular material satisfies one or more of the following conditions: (1) X1, X2, Y1 and Y2 are each independently selected from one of hydrogen, C1-C6 alkyl, C1-C6 alkoxy, halogen, C2-C6 alkenyl and C2-C6 alkynyl; (2) R1 and R2 are each independently selected from C1~C6 alkyl; (3) L1 and L2 are each independently selected from a C2-C6 alkylene group and a phenylene group; (4) A1 and A2 are each independently selected from a phosphoric acid group and a carboxylic acid group.

6. The solar cell according to claim 5, characterized in that: The self-assembled monomolecular material is selected from one or more of the following structural formulas: .

7. The solar cell according to claim 1, characterized in that The hole transport layer is anchored on the substrate surface through the self-assembled monomolecular material; and / or, The thickness of the hole transport layer is 10nm-30nm.

8. The solar cell according to any one of claims 1 to 3 and 5 to 7, characterized in that: The solar cell is a single-junction cell, and the solar cell comprises a substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer and a counter electrode which are stacked in sequence; or The solar cell is a stacked cell, and the solar cell comprises: a top cell, a bonding layer and a bottom cell stacked in sequence, the top cell comprises the hole transport layer and the perovskite light absorption layer, and the bonding layer comprises the substrate.

9. A method for preparing a solar cell, characterized in that: The steps include: Obtaining a dispersion comprising inorganic nanoparticles, a self-assembled monomolecular material and a dispersion solvent; Applying the dispersion on the surface of the substrate, annealing, and anchoring at least part of the self-assembled monomolecular material on the surface of the inorganic nanoparticles to prepare a hole transport layer; A perovskite light-absorbing layer is formed on the surface of the hole transport layer to prepare a solar cell.

10. The method for preparing a solar cell according to claim 9, characterized in that: One or more of the following conditions are met: (1) The mass ratio of the self-assembled monomolecular material to the inorganic nanoparticles is (1-5): 100; (2) The inorganic nanoparticles include one or more of doped or undoped nickel oxide nanoparticles, cuprous iodide nanoparticles, cuprous thiocyanate nanoparticles, copper oxide nanoparticles, cuprous oxide nanoparticles, copper sulfide nanoparticles and antimony-doped tin oxide nanoparticles; (3) The self-assembled monomolecular material is selected from one or more of the following structural formulas: and ; In the formula, X1, X2, Y1 and Y2 are each independently selected from hydrogen, C1~C 10 Alkyl, amino, nitro, C1~C 10 Alkoxy, halogen, C2~C 10 Alkenyl and C1~C 10 One of the alkynyl groups; R1 and R2 are each independently selected from hydrogen and C1~C 10 One of the alkyl groups; L1 and L2 are each independently selected from C2 to C 18 One of an alkylene group and a phenylene group; A1 and A2 are each independently an anchoring group; (4) In the dispersion, the concentration of the inorganic nanoparticles is 15 mg / mL to 30 mg / mL; (5) The dispersing solvent includes an alcohol solvent; (6) The annealing step includes: heating annealing at 100°C to 150°C for 10 min to 60 min.

11. A solar cell module, characterized in that: The invention comprises a plurality of solar cells connected in series, wherein the solar cell is a solar cell as claimed in any one of claims 1 to 8 or prepared by the preparation method as claimed in any one of claims 9 to 10.

12. A photovoltaic module, characterized in that: The invention comprises the solar cell according to any one of claims 1 to 8, the solar cell prepared by the preparation method according to any one of claims 9 to 10, or the solar cell module according to claim 11.